UMP, Ulm University of Applied Sciences collaborate on German Model campus sustainability programme - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
FRANKFURT, 15 July 2022 - Networking collaboration for campus sustainability between Universiti Malaysia Pahang (UMP) and Ulm University of Applied Sciences (THU), Germany will develop a campus sustainability model with a German Engineering education that is based on the Fachhochschule in the national higher education system.